The Role of Folklore in Building Character and Early Childhood Language Skills - Juli Rohmat (LP3M STAI MA'ARIF MAGETAN, 2024)
This study explores the role of folklore in shaping the character and language skills of early childhood learners. Folklore, rich in cultural values and moral lessons, serves as an effective medium for instilling virtues such as empathy, respect, and responsibility in young children. Through storytelling, children not only engage with the narratives but also enhance their linguistic abilities, including vocabulary acquisition, comprehension, and narrative skills. The research employs a qualitative approach, gathering data through observations, interviews with educators, and analyses of children's responses during storytelling sessions. The findings indicate that incorporating folklore into early education significantly promotes moral development and language proficiency among children. Furthermore, it highlights the necessity of integrating cultural narratives into educational practices to foster a holistic learning environment. The study underscores the importance of folklore as a vital tool for educators in nurturing the character and language skills of young learners, ultimately contributing to their overall development